Evaluation of Structure–Function Relationships of Aggregation-Induced Emission Luminogens for Simultaneous Dual Applications of Specific Discrimination and Efficient Photodynamic Killing of Gram-Positive Bacteria - Kang, Miaomiao; Zhou, Chengcheng; Wu, Shuangmei; Yu, Bingran; Zhang, Zhijun; Song, Nan; Lee, Michelle Mei Suet; Xu, Wenhan; Xu, Fu-Jian; Wang, Dong; Wang, Lei; Tang, Ben Zhong (Journal of the American Chemical Society, 2019)
Bacterial infectious diseases, especially those caused by Gram-positive bacteria, have been seriously threatening human health. Preparation of a multifunctional system bearing both rapid bacterial differentiation and effective antibacterial effects is highly in demand, but remains a severe challenge. Herein, we rationally designed and successfully developed a sequence of aggregation-induced emission luminogens (AIEgens) with orderly enhanced D–A strength. Evaluation of structure–function relationships reveals that AIEgens having intrinsic positive charge and proper ClogP value are able to stain Gram-positive bacteria. Meanwhile, one of the presented AIEgens (TTPy) can generate reactive oxygen species (ROS) in extraordinarily high efficiency under white light irradiation due to the smaller singlet–triplet energy gap. Thanks to the NIR emission, excellent specificity to Gram-positive bacteria, and effective ROS generation efficiency, TTPy has been proved to perform well in selective photodynamic killing of Gram-positive bacteria in vitro, such as S. aureus and S. epidermidis, even in S. aureus-infected rat wounds.